Income Tax – Sale of a going concern: Assumed Contingent Liabilities Clarification versus legislative reforms - Marais, Abrianne (Department of Finance and Tax, 2020)
The income tax consequences that flow from the assumption of contingent liabilities as part of the sale of a going concern is a contentious matter that continues to frustrate sellers and purchasers. The challenges faced by sellers and purchasers include inherent mismatches between the objects of accounting practice and that of income tax legislation; inconsistent policy formulation by National Treasury (Treasury) and the South African Revenue Service (SARS), and income tax legislation and case law that do not adequately recognise the economic effect of these transactions for sellers and purchasers. These, and other, challenges are highlighted and unpacked in this study by evaluating accounting standards, the Income Tax Act 58 of 1962 (ITA), case law and publications by SARS. In recent years there have been increasing calls for Treasury and Parliament to intervene by means of legislative reforms and for SARS to issue guidelines, in order to provide clarity regarding the income tax consequences for sellers and purchasers. New provisions and amendments to the ITA were proposed in the Draft Taxation Laws Amendment Bill of 2011 (draft Bill). The proposed legislative reforms were however withdrawn before the Taxation Laws Amendment Bill of 2011 was introduced in Parliament. Interpretation Note 94: Contingent Liabilities Assumed in the Acquisition of a Going Concern (IN94) was published by SARS during the latter part of 2016, with the aim of setting out principles which can serve as an interpretative guide for the determination of the income tax consequences for sellers and purchasers. This study investigates whether IN94 adequately addresses the challenges highlighted in this dissertation. The Davis Tax Committee, in its Report on the Efficiency of South Africa's Corporate Income Tax System, states that while SARS has attempted to address some of the shortcomings in respect of the taxation of contingent liabilities through interpretation notes and rulings, this is unsatisfactory as it is the legislation which requires amendment in order to address the shortcomings. In the final part of this study, the legislative reforms proposed in the draft Bill iv are evaluated, and the case is made for the reconsideration of comprehensive legislative reforms in order to create more certainty for sellers and purchasers.